Answer: (E) 60J
Step-by-step explanation:
According to the question
Mx = My/2
2Mx = My
(Where Mx is the mass of X and My is the mass of Y)
Y is twice as heavy as X
Kinetic energy of an object =
1/2mv^2
Kinetic energy of X
Ex = 1/2Mx.V^2... Eqn 1
Where V is the velocity
(We assume that the velocity is equal for both objects, there is absence of friction. They have been set in motion by force from the same spring)
Kinetic energy for Y
Ey = 1/2My.V^2.....eqn 2
But My = 2Mx
Ey = 1/2(2Mx.V^2)
Ey= Mx.V^2.....eqn 3
From eqn 1
Ex = 30
30 = 1/2Mx.V^2
Multiply through by 2
60= Mx.V^2
Mx= 60(V^-2)......eqn 4
Put eqn 4 in eqn 3
Replace the value of Mx
Ey= 60(V^-2).V^2
Ey = 60 (V^-2+2)
Ey = 60J